Size effects in the transition region and the beginning of the upper shelf for ferritic steels - Perez Ipiña, Juan Elias (2010)
The determination of a characteristic fracture toughness value for ferritic steels in the ductile-to-brittle transition regime becomes difficult due to the scatter observed in the results. As the temperature increases, ductile mechanisms become more active and sometimes no brittle fracture occurs. Close to the upper shelf, and contrary to what happens when only cleavage occurs, the scatter diminishes as the temperature increases, and it is also size-dependent: more scatter is found for larger sizes than for smaller specimens. An interpretation of the phenomena that takes place from the transition region up to the beginning of the upper shelf is presented in this work. This interpretation explains the difference in scatter and toughness among different sample sizes, and it also validates that the beginning of the upper shelf is dependent on the size of the sample or structure. Results from the Euro Dataset Round Robin were used to validate this interpretation.